Influence of intelligent transportation system in a road infrastructure - Marcelo Franco Porto (2016)
Over the past 30 years, it has seen the development of Intelligent Transportation Systems - ITS around the world in different ways, designed to reach new transport patterns, and with it, the concept is gaining more credibility among users. With this technology, the goal is to establish communications between user, vehicle and infrastructure in an integrated manner and thus provide a supply of a more sustainable and efficient transport. This paper introduces the basic concepts of ITS, its Architecture, and shows the most recent studies in the area. Property use of this system can bring gains in sustainability, mobility and security, being a breakthrough for transport system.